PENERAPAN MODEL PEMBELAJARAN KOPERATIF TIPE JIGSAW MENINGKATKAN PROSES DAN HASIL BELAJAR SISWA - APDOLUDIN APDOLUDIN; RANDI EKA PUTRA (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
The problem in this study is the low learning process and outcomes of students in science learning, this is evidenced by the results of observations and school documentation which shows that out of 19 students only 47% fulfilled the KKM. This research was conducted in Class V SDN 188 / VIII Wiroto Agung. The purpose of this study was to describe and determine the application of the jigsaw cooperative model in increasing the activity and learning outcomes of science learning in Class V. The method used in this study was classroom action research (PTK). This study consisted of 2 cycles, each cycle carried out through 4 stages, namely planning, acting, observing and reflecting and consisted of 2 meetings. The results of the research can be explained as follows: (1) the application of the jigsaw cooperative model in learning activities seen from the observation sheet, namely the first cycle of the teacher aspect of 84% and the student aspect of 57%, while in the second cycle there was an increase of 91% of the teacher and student aspects% who have reached the indicators of success. (2) the application of the jigsaw cooperative model in learning in cycle I is still not optimal. This can be seen from the test results in cycle I only 32% of students who meet the KKM and in cycle II an increase is 79% of students who meet the KKM, thus it can be concluded that the jigsaw cooperative model can improve the process and learning outcomes at SDN 188 / VIII Wiroto Agung.